Development of Palembang Local Wisdom Photography Gallery - Syarifuddin Syarifuddin; Adhitya Rol Asmi; Sani Safitri (STAI Hubbulwathan Duri, 2022)
With the theme of web-based photography gallery, this study aims at collecting and centralising scattered data on local wisdom in Palembang and Surakarta. With both having long history in their existence, Palembang and Surakarta are home to many and various cultural heritage. This study tries to collect information about these and centralise them into a valid, practical and effective photography gallery that will help with students' learning. This is because in developing a medium like this, not only can it be a way of preserving cultural heritage, the end result of collected data and information can be a rich, interesting source of learning materials. All the steps taken in this study all lead to the main objective mentioned earlier, collecting and centralising historical photos of Palembang and Surakarta across a span of time periods in a way that is comprehensive and interesting, especially in terms of academics or education. This study uses the ADDIE Model for its research and development process. The data is collected through individual interviews (culture practitioners, historians, local residents of Palembang and Surakarta, etc.) as well as reviewing existing websites of the same category. The end product of this research has gone through expert validation in terms of materials, media and language, and is considered valid. After that the validated product underwent one-to-one and small group evaluation to assess its practicality, effectiveness and attractiveness.